Swedish Career Counsellor Students’ Descriptions of their Future Professional Identity - Helena Rehn (Nordic Journal of Transitions, Careers and Guidance)
The aim of this study is to analyse how Swedish students in their final semester of a career counsellor programme describe their future professional identity based on experiences from their education and from participating in counsellor activities. The study builds on qualitative interviews with 23 career counsellor programme students. Professional identity theories are used as the theoretical framework. The results show that through the theoretical part of their education students acquired a special combination of knowledge, abilities and approaches they perceived the professional culture requires, which they described in a coherent manner. The students expressed loyalty to the person being counselled, a desire to behave neutrally as well as to pay attention to and counteract one’s own and societal norms and structures in the conversation as important parts of the professional identity. Abstrakt Syftet med studien är att analysera hur svenska studenter som läser sista terminen på studie- och yrkesvägledarprogram beskriver sin kommande professionella identitet utifrån sina erfarenheter från utbildningen och vägledande verksamhet. Studien bygger på kvalitativa intervjuer med 23 studenter. Som teoretiskt ramverk används Professionella identitetsteorier. Resultatet visar att studenterna genom den teoretiska delen av sin utbildning tillägnat sig en speciell kombination av kunskaper, förmågor och förhållningssätt som de upplevt att yrkeskulturen kräver, vilket de beskrev på ett samstämmigt sätt. Studenterna uttryckte en lojalitet mot den som vägleds, en vilja att alltid förhålla sig neutralt liksom att uppmärksamma och motverka egna och samhälleliga normer och strukturer i samtalet som viktiga delar av den professionella identiteten. Nyckelord: studie-och yrkesvägledarstudenter; professionell identitet; studieoch yrkesvägledarutbildning; kunskap; förhållningssätt